2011
DOI: 10.1097/1939-4551-4-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Chronic Respiratory Diseases (CRD) in Middle East and North Africa (MENA)

Abstract: Chronic respiratory diseases involve a heterogenous group of diseases, including, chronic obstructive pulmonary disease (COPD), asthma, sleep apnea syndrome, pulmonary hypertension, and many occupational diseases. They affect more than one billion people worldwide. Their medical, social, and economic impacts are heavy, especially in developing countries such as Middle East and North Africa countries, where they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“… 43 Chan-Yeung et al estimate a prevalence of 179 per 100,000 in Africa and 301 per 100,000 in Eastern Mediterranean countries, less than that of America and Europe. 7 , 44 However, a recent systematic analysis by Adeolaye et al reported the estimated median prevalence of COPD in persons aged 40 years or older as 13.4% (range 9·4% to 22·1%), translating into 26.3 million (18.5 to 43.4 million) cases of COPD in SSA. 45 Within the SSA region, Cape Town in South Africa had the highest prevalence estimates published within the international BOLD study, as GOLD stage II prevalence was 22.2% in men above 40 years.…”
Section: Copd and Asthma Disease Burdenmentioning
confidence: 99%
See 2 more Smart Citations
“… 43 Chan-Yeung et al estimate a prevalence of 179 per 100,000 in Africa and 301 per 100,000 in Eastern Mediterranean countries, less than that of America and Europe. 7 , 44 However, a recent systematic analysis by Adeolaye et al reported the estimated median prevalence of COPD in persons aged 40 years or older as 13.4% (range 9·4% to 22·1%), translating into 26.3 million (18.5 to 43.4 million) cases of COPD in SSA. 45 Within the SSA region, Cape Town in South Africa had the highest prevalence estimates published within the international BOLD study, as GOLD stage II prevalence was 22.2% in men above 40 years.…”
Section: Copd and Asthma Disease Burdenmentioning
confidence: 99%
“…Although there is a paucity of good epidemiological data, there appears to be substantial differences in prevalence estimations between countries in the region. 44 , 49 Tunisia reportedly has a prevalence of 3.8% compared to 125 per 100,000 people in Algeria and 5.6% in Lebanon. 44 A recent study from Saudi Arabia estimated COPD prevalence to be 2.4% in the general population and 14.2% among smokers (56).…”
Section: Copd and Asthma Disease Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…According to 2008 global burden of disease (GBD) estimates, over 600 million have allergic rhinitis, 300 million people have asthma, and 210 million people have COPD (1,6,7). Th e WHO also estimates that COPD is responsible for about 3 million deaths globally in 2011, accounting for about 9.1% of all NCDs deaths (8).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) represents a major public health problem and one of the leading causes of morbidity and mortality worldwide. The population prevalence of COPD is growing in developing countries and especially in North Africa [ 1 – 2 ]. Among the major causes of COPD, the role of tobacco smoking is well recognized and accordingly, recent studies of COPD have been largely focused on the smoking rather than the non-smoking population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%